UNIT 15I.1 Avian Bornaviruses: Diagnosis, Isolation, and Genotyping. Issue 1 (1st August 2014) - Guo, Jianhua; Payne, Susan; Zhang, Shuping; Turner, Debra; Tizard, Ian; Suchodolski, Paulette
Abstract: These protocols apply to all currently known genotypes of avian bornavirus (ABV). First, they include four basic protocols for molecular techniques that should enable an investigator to detect ABV infection in a live or dead bird. These include both reverse transcriptase and real‐time PCR assays. Second, they include three protocols enabling ABV infections to be diagnosed by serologic techniques including indirect immunofluorescence assays, western blotting, and enzyme‐linked immunoassays. Third, they also include methods by which ABV can be isolated from infected bird tissues by culture in primary duck embryo fibroblasts, as well as in other avian cell lines. Finally, as part of a diagnostic workup, any virus detected should be genotyped by sequencing, and a protocol for this is also provided. Curr. Protoc. Microbiol . 34:15I.1.1‐15I.1.33. © 2014 by John Wiley & Sons, Inc.